Determinants of chemical fertilizer use in Nepal: Insights based on price responsiveness and income effects - Takeshima, Hiroyuki; Adhikari, Rajendra Prasad; Kaphle, Basu Dev; Shivakoti, Sabnam; Kumar, Anjani (International Food Policy Research Institute, 2016)
Although overall chemical fertilizer use has grown steadily in Nepal in the past two decades, much of that growth has occurred in the Terai agroecological belt while use has stagnated in the Hills and the Mountains regions. Differences in chemical fertilizer use intensity between the Terai and the latter regions are typically pronounced among medium-to-large-size farmers. Using three rounds of the Nepal Living Standards Survey as well as secondary data, we examine the determinants of inorganic fertilizer (urea and DAP) use, as well as the marginal income returns from fertilizer use at the farm-household level. Similarities in soil and climate between farm locale and Agriculture Research Station locale seem to increase demand for fertilizer—even after controlling for distance to those stations. Most important, demand for chemical fertilizer is affected by the real fertilizer price (particularly since the 2003 NLSS survey), but the price response is relatively weaker in the Hills and Mountains, suggesting that returns to fertilizer may be generally low in those regions, and that reducing fertilizer price through subsidies on fertilizer or transportation may not substantially increase fertilizer use. This is confirmed by assessment of the returns to chemical fertilizer use estimated through generalized propensity score matching and ordinary propensity score matching. The findings cast doubt on the effectiveness of fertilizer subsidies as an instrument for stimulating chemical fertilizer use in Nepal, particularly among medium-to-large-scale farmers in the Hills, and point toward alternative measures like increased research and development into technologies that raise overall returns to chemical fertilizer.